2006
DOI: 10.1152/ajplung.00345.2005
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptide neuromedin U activates eosinophils and is involved in allergen-induced eosinophilia

Abstract: Neuromedin U (NMU) is a neuropeptide expressed not only in the central nervous system but also in various organs, including the gastrointestinal tract and lungs. NMU interacts with two G protein-coupled receptors, NMU-R1 and NMU-R2. Although NMU-R2 is expressed in a specific region of the brain, NMU-R1 is expressed in various peripheral tissues, including immune and hematopoietic cells. Our recent study demonstrated an important role of NMU in mast cell-mediated inflammation. In this study, we showed that airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 27 publications
(31 reference statements)
2
63
0
Order By: Relevance
“…NmU mRNA has been detected in antigen-presenting cells, particularly monocytes and dendritic cells, and NMUR1 mRNA has been detected in T and natural killer cells, and also at lower concentrations in other immune and hematopoietic cells such as eosinophils and mast cells (14,122 ), suggesting a role in the immune response. NmU was first shown to induce synthesis and release of several different cytokines [interleukin-4 (IL-4), IL-5, IL-6, IL-10, and IL-13) from a mouse T-helper 2 cell line in an NMUR1-dependent fashion (123 ).…”
Section: Immune Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…NmU mRNA has been detected in antigen-presenting cells, particularly monocytes and dendritic cells, and NMUR1 mRNA has been detected in T and natural killer cells, and also at lower concentrations in other immune and hematopoietic cells such as eosinophils and mast cells (14,122 ), suggesting a role in the immune response. NmU was first shown to induce synthesis and release of several different cytokines [interleukin-4 (IL-4), IL-5, IL-6, IL-10, and IL-13) from a mouse T-helper 2 cell line in an NMUR1-dependent fashion (123 ).…”
Section: Immune Regulationmentioning
confidence: 99%
“…The fact that NmU is involved in secretion of proinflammatory cytokines explains its role as an inflammation promoter: local NmU administration induces progressive vasodilation and edema, while NmU-deficient mice show decreased extravasation mediated by substance P (122 ). Aside from localized inflammatory phenomena, mice deficient in NmU showed decreased mortality following lipopolysaccharide-induced septic shock, and this was due to reduced circulating IL-6 concentrations (124 ).…”
Section: Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we and others have reported that NmU induces an intracellular calcium ion (Ca 2ϩ ) flux 14,17,25,26,30,31 and that mobilized Ca 2ϩ can directly activate the classic PKC-␤II isoform to modulate hematopoietic cell proliferation and differentiation, 32,33 we determined the ability of NmU to activate PKC-␤II. Using immunofluorescence microscopy, we observed PKC-␤II in the cytoplasm of unstimulated K562 ( Figure 4A) and CD34 ϩ cells ( Figure 4C).…”
Section: Nmu Activates Pkc-␤ii Hematopoietic Cellsmentioning
confidence: 99%
“…16,18,21 In the gut, NmU has been reported to regulate local blood flow and ion transport. [22][23][24] Although NmU has been reported to stimulate cytokine production in the murine Th2-type T-cell clone D10.G4.1 25 and promote mast cell-mediated inflammation, 26 the physiologic function of NmU during hematopoiesis in the bone marrow remains ill defined. Given that c-Myb is required during erythropoiesis and that NmU is a candidate Myb target gene, we postulated that c-Myb induces NmU expression in normal hematopoietic cells to facilitate erythropoiesis.…”
Section: Introductionmentioning
confidence: 99%